2017
DOI: 10.1167/iovs.17-21592
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Association Between Peripapillary Bruch's Membrane Shape and Intracranial Pressure

Abstract: PurposeThe purpose of this study was to determine if there is a quantitative relationship between chronic intracranial pressure (ICP) and peripapillary Bruch's membrane (pp-BM) shape and to determine whether change in pp-BM shape can be detected within 1 hour after ICP lowering by lumbar puncture (LP).MethodsIn this study, 30° nasal-temporal optical coherence tomography B-scans were obtained within 1 hour before and after LP in 39 eyes from 20 patients (age = 23–86 years, 75% female, ICP [opening pressure] = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…197 Gampa and colleagues analyzed 20 patients undergoing LP and found a detectable downward bowing of the Bruch membrane complex within 1 hour of lowering the ICP, supporting the concept that it is a flexible and dynamic structure that acutely changes with alterations in CSF pressure. 54 Anand and coworkers also found a decrease in the Bruch membrane complex angulation immediately after LP in 5 patients with IIH. 2 In addition to the Bruch membrane complex orientation, there are structural changes in the LC in response to changes in CSF pressure.…”
Section: 2mentioning
confidence: 86%
“…197 Gampa and colleagues analyzed 20 patients undergoing LP and found a detectable downward bowing of the Bruch membrane complex within 1 hour of lowering the ICP, supporting the concept that it is a flexible and dynamic structure that acutely changes with alterations in CSF pressure. 54 Anand and coworkers also found a decrease in the Bruch membrane complex angulation immediately after LP in 5 patients with IIH. 2 In addition to the Bruch membrane complex orientation, there are structural changes in the LC in response to changes in CSF pressure.…”
Section: 2mentioning
confidence: 86%
“…70 Research studies have demonstrated that quantitative OCT parameters of the optic nerve head such as optic nerve head volume and eye shape relate to other optic nerve head measures and CSF pressure. 71,72 Furthermore, OCT measures of optic nerve swelling normalized in association with treatment provided in the IIHTT 73 ; however, these are not considered established diagnostic tests as yet.…”
Section: Fundus Photographymentioning
confidence: 99%
“…Morphological quantifications from the OCT scans (e.g., retinal thickness and lamina cribrosa depth) facilitate the diagnosis and treatment planning of many blinding diseases [5][6][7][8]. The shape of peripapillary retinal pigment epithelium-basement membrane (ppRPE/BM) layer has attracted much attention due to its relationship with ICP fluctuations [9]. Specifically, Sibony et al used a manual segmentation method for selected patients with symmetrical temporal-nasal scans, and observed that the ppRPE/BM layer exhibited a deeper V-shape following the ICP-lowering intervention [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are several limitations to the methods used by these groups. The principal component analysis (PCA) method was generally used in the aforementioned shape analysis [9,11]. However, the principal components depend on the choice of dataset [12,13], and the shape analysis results highly depend on the choice of OCT scan direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation